PEMBELAJARAN PENGELASAN LAS BUSUR LISTRIK BERBASIS PROJECT BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA - Purwanto, Purwanto; Samani, Muchlas; Estidarsani, Nanik (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2015)
ABSTRACT This research is an experimental research which aims to find the information of the students? critical thinking, affective learning outcomes, cognitive learning outcomes, psychomotor learning outcomes and response after the students?s are given project-based learning. This research uses experimental research by using Quasi Experimental Design by using Time Series Design. The subjects of the research are eleventh grade students? of welding engineering skill of Vocational School 6 Samarinda, East Kalimantan in the odd semester of academic year of 2014/2015. There are 31 students?. The data is collected through pre-test and post-test to find the students? critical thinking skill, affective learning outcomes, cognitive learning outcomes, and psychomotor learning outcomes. The response questionnaire is used to find the interest, innovation, pleasure, easiness, clarity and students? interest to the learning process.The data is analyzed by using N-Gain descriptive analysis and t-Test. The result of the research shows that the research instrument which is used is valid. The result shows that the average students? critical thinking is in the high categorized > 0,70. The other result shows that the project based learning model gives the effect for the affective, cognitive, and psychomotor learning outcomes. Three of them are in the category of pass. The students? response in the project based learning is good. Based on the result, it can be concluded that project based learning for electric arc welding improve the critical thinking of vocational school and can make the students? pass the affective, cognitive, and psychomotor learning outcomes. Keywords: Project Based Learning, Critical Thinking Skill, Students? Learning Outcomes.